55m-4=-6(m+2)

Simple and best practice solution for 55m-4=-6(m+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 55m-4=-6(m+2) equation:


Simplifying
55m + -4 = -6(m + 2)

Reorder the terms:
-4 + 55m = -6(m + 2)

Reorder the terms:
-4 + 55m = -6(2 + m)
-4 + 55m = (2 * -6 + m * -6)
-4 + 55m = (-12 + -6m)

Solving
-4 + 55m = -12 + -6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '6m' to each side of the equation.
-4 + 55m + 6m = -12 + -6m + 6m

Combine like terms: 55m + 6m = 61m
-4 + 61m = -12 + -6m + 6m

Combine like terms: -6m + 6m = 0
-4 + 61m = -12 + 0
-4 + 61m = -12

Add '4' to each side of the equation.
-4 + 4 + 61m = -12 + 4

Combine like terms: -4 + 4 = 0
0 + 61m = -12 + 4
61m = -12 + 4

Combine like terms: -12 + 4 = -8
61m = -8

Divide each side by '61'.
m = -0.131147541

Simplifying
m = -0.131147541

See similar equations:

| .8b+1.9=5.5-.4b | | 5(-2+2)=3(-4+6) | | 10=6x-2x-8 | | -35=x-18 | | .8b+1.9=5.5-4b | | 2x+x+30=90 | | -35=x+18 | | 4x+4=-20-2x | | 3/5--2/5= | | 60+p=70 | | 6s-4=-20 | | y=3/4*3+1 | | 4a+1-8a=9 | | 8mn-5m= | | 3l+y=5+5l | | 88-8m=8m+88 | | -16.5h+9.25h=21.75 | | -13y-34y= | | y=3/4(3)+1 | | 2m+3m-6=7m-34 | | 46+y=136 | | 14mn-19mn= | | 3x=7y-2 | | 4y-15y=22 | | 10y^2+28y-5=0 | | -x-45=47 | | 5a^2-17+14=0 | | 9+d=23 | | 4(7-4k)+2k=-36-6k | | 2+4(x-5)=5 | | 2(3.5)+2w=31 | | x+20+x+10=180 |

Equations solver categories